1994
DOI: 10.1002/hep.1840190602
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis D virus infection with low and high doses of interferon-α2a: Utility of polymerase chain reaction in monitoring antiviral response

Abstract: We examined the efficacy of decreasing high doses (beginning at 18 MU/day) of interferon-alpha 2a vs. that of daily low doses (3 MU) in the treatment of chronic hepatitis delta virus infection. Patients treated with 18 MU had a somewhat higher frequency of normalization of serum ALT levels than patients treated with low doses (31% and 12%, respectively, on an intention-to-treat basis). A decrease in the percentage of hepatitis D virus RNA positivity was observed in both groups at the end of treatment. Thus, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 15 publications
0
42
0
2
Order By: Relevance
“…The diagnosis of HDV infection usually relies on the detection of specific anti-HDV antibodies, with the presence of anti-HDV immunoglobulin M (IgM) reflecting ongoing viral replication. However, the serological approach for the detection of virus replication lacks sensitivity (8,25). The HDV antigen is rarely detected in the serum, except in cases of acute infections (prior to the antibody response) or chronic infections in severely immunosuppressed patients (17).…”
mentioning
confidence: 99%
“…The diagnosis of HDV infection usually relies on the detection of specific anti-HDV antibodies, with the presence of anti-HDV immunoglobulin M (IgM) reflecting ongoing viral replication. However, the serological approach for the detection of virus replication lacks sensitivity (8,25). The HDV antigen is rarely detected in the serum, except in cases of acute infections (prior to the antibody response) or chronic infections in severely immunosuppressed patients (17).…”
mentioning
confidence: 99%
“…At present, interferon is the only option for the treatment of chronic hepatitis D. Since most patients have advanced disease and cirrhosis, the response rate to interferon (IFN) therapy is not high (less than 10% with 1-year IFN therapy [63][64][65]). Therapeutic efficacy increases when higher dose of interferon alpha is administered for prolonged periods (12-24 months) [63][64][65][66]. As described in an interesting case report a 12-year high-dose IFN treatment resulted in the complete resolution of HDV infection with remission of liver fibrosis and disappearance of HBV and HDV from serum [67].…”
Section: Current Therapiesmentioning
confidence: 92%
“…Traditionally, conventionally IFN proofed to be effective in chronic hepatitis D in the early 1990s [32][33][34][35] . Also, a placebo-controlled trial reported in 2005 could show a benefit for conventional IFN in a small cohort [36] .…”
Section: Treatment Of Delta Hepatitismentioning
confidence: 99%